Chip war : the fight for the world's most critical technology / Chris Miller. - Miller, Chris (Research fellow) (Simon & Schuster, 2022)
'Chip War' examines why control of the microchip industry has been the driving force of Western economic and military success, and the potential threats posed by China's actions.